LANGUAGE ADJUSTMENT ON A CONTACT SITUATIONS BETWEEN NATIVE SPEAKERS AND ADVANCED JAPANESE LEARNERS: A COMPARISON WITH NATIVE SPEAKERS SITUATIONS (æ¯èªžè©±è€…ã¨ä¸Šç´šæ—¥æœ¬èªžå¦ç¿’è€…ã®æŽ¥ç¶šå ´é¢ã«ãŠã‘ã‚‹è¨€èªžèª¿æ•´ï¼šæ¯èªžå ´é¢ã¨ã®æ¯”è¼ƒ) - Christopher, Dwiky Yoseph (Universitas Pendidikan Indonesia (Indonesia University of Education), 2018)
The situations where both native and non-native speakers participate in a conversation are called contact situations. In these situations, both native and non-native speakers make verbal behaviour adjustments to achieve a smooth conversation. Adjustments by native speakers usually are made in form of Foreigner Talk (FT) while adjustments by non-native speakers made by performing communication strategies (CS). The common point between FT and CS comes from the lack of language ability or resource deficit. However, higher the non-native speakersâ€™ second language proficiency, the adjustments made by both speakers are expected to be more complex. This paper is aiming to investigate those verbal adjustments made by native speakers in the contact situations with advanced learners / non-native speakers. To do it, this paper is employing n-gram method to gain the database of collocation and its occurrence frequency. The data for this research are Nagoya University Conversation Corpus and Nagoya University Japanese Learners Corpus. From the data, this paper found verbal behaviour adjustments which takes form in expressions such are â€œunâ€ which coined at the end of own utterance, â€œtokaitteâ€, and â€œsounandaâ€.